Optimization of in vitro culture conditions of common carp germ cells for purpose of surrogate production - Xie, Xuan; Franěk, Roman; Pšenička, Martin; Chen, Fan; Kašpar, Vojtech (Frontiers in Veterinary Science, 2022)
Common carp (Cyprinus carpio) is the fourth most-produced fish species in aquaculture and frequently used model species with significant effort invested in development of biotechnological applications. In present study we attempted to establish an in vitro germ cell culture condition for short term cell culture, which could facilitate further applications such as surrogacy or gene manipulation. Basal media and different types of feeder cells were investigated to optimize carp germ cell culture condition to favor maintenance of mitotic proliferation. Results indicated that germ cells cultured with hESC media and RTG2 cell line as feeder possessed significantly higher proliferation and survival rate compared to that cultured with StemPro media and Sertoli cell line as feeder. In addition, we compared two dissection strategies to compare risk of cell culture contamination and body cavity was open from dorsal part or from ventral part. As a result, carp open from dorsal part can minimizes the risk of contamination. In summary, this study brings up the first optimization of cultivation of germ cells in common carp this brings new possibilities in utilization of specific techniques in breeding of this species of high commercial interest as well as frequently used model species. Results obtained in this study are important for implementation of new strategies in common carp breeding, conservation of genetic resources, restoration of lines or development of clonal and isogenic carp lines.